It Does Not Stop at Treaties: Filling the Void of Indigenous Governance - Yamina Sfiat (Journal of Social Equity and Public Administration)
The field of public administration has rarely investigated the complexities of intergovernmental relationships among Tribal governments. Very little is known about how Tribal governments function as their own administration or as an administration within another nation, or about the many intricacies and histories centralized within that dynamic. Not understanding how these governments function, how they overlap, or how the United States often works against sovereign nations is detrimental to any policy created with the intent of service to Tribal governments. This article seeks to address this issue and provides an agenda of questions for scholars to explore. Tribal public administration must be placed at the core of public administration rather than at the margins, and in doing so, public administration as a field must prioritize Indigenous voices.